The History of the Development of Kauman Village with Islamic Values Characteristics in Semarang City from 1970- 2000: Sejarah Perkembangan Kampung Kauman Dengan Karakteristik Nilai– Nilai Islam Di Kota Semarang Tahun 1970- 2000 - Adani, Syamaidzar; Sodiq, Ibnu (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This article explores the origins, development, and socio-cultural transformation of Kampung Kauman in Semarang City between 1970 and 2000. Kampung Kauman is a traditional settlement that serves not only as a religious center for urban Muslim communities but also as a symbol of acculturation between Islamic traditions and Javanese urban planning. Unlike other Kauman areas such as those in Yogyakarta or Surakarta, which developed under royal authority, Kauman in Semarang evolved within a more complex colonial context—adjacent to trade centers and the harbor. The modernization process since the 1970s shifted the community’s economic orientation from religious-based professions to trade and services, yet religious identity was preserved through the strengthening of social institutions like mosques, religious study groups, and sharia-based cooperatives. The article further illustrates how Islamic cultural values were maintained through social practices, religious education, religious arts, and the active role of women in preserving tradition amid modernization. Using historical and sociological approaches, this study reveals that the revitalization of Islamic identity in Kauman is a result of dynamic and contextual adaptation processes.